An Item Response Theory Analysis of the Community of Inquiry Scale - Horzum, Mehmet Barış; Uyanik, Gülden Kaya (International Review of Research in Open and Distributed Learning)

(untitled) (Athabasca University Press (AU Press), 2015)
The aim of this study is to examine validity and reliability of Community of Inquiry Scale commonly used in online learning by the means of Item Response Theory. For this purpose, Community of Inquiry Scale version 14 is applied on 1,499 students of a distance education center’s online learning programs at a Turkish state university via internet. The collected data is analyzed by using a statistical software package. Research data is analyzed in three aspects, which are checking model assumptions, checking model-data fit and item analysis. Item and test features of the scale are examined by the means of Graded Response Theory. In order to use this model of IRT, after testing the assumptions out of the data gathered from 1,499 participants, data model compliance was examined. Following the affirmative results gathered from the examinations, all data is analyzed by using GRM. As a result of the study, the Community of Inquiry Scale adapted to Turkish by Horzum (in press) is found to be reliable and valid by the means of Classical Test Theory and Item Response Theory.